Effects of free feeding time system and energy level to improve the reproductive performance of lactating sows during summer - Kwang Yeol Kim; Yo Han Choi; Abdolreza Hosseindoust; Min Ju Kim; Joseph Moturi; Tae Gyun Kim; Chang Hyun Song; Jun Hyung Lee; Byung Jo Chae (Journal of Animal Science and Technology, 2020)
The reproductive performance of lactating sows was investigated by using different feeding methods including conventional feeding (CF, 3 times/d) or free feeding (FF), and different dietary energy level including low energy (LE: 3,300) or high energy (HE: 3,400 kcal/kg) during the hot season. A total of twenty-eight crossbred (Yorkshire × Landrace) sows were distributed into four treatments as a 2 × 2 factorial arrangement. Sows in the FF group showed lower body weight and backfat loss (p < 0.05) compared with the CF group. Backfat loss during lactation was lower (p < 0.05) in sows fed HE diet than in that fed LE diet. There were no significant differences in litter survival rate and weaning to estrus interval, but the litter weight at weaning was improved (p < 0.05) in FF and HE sows. Hence, it is concluded that using the free-feeding system or increased dietary energy density leads to improved sow performance during hot ambient temperature.